Fibrous dysplasia in the alveolar crest of edentulous site and the curettage for future implant placement: a case report - Hao Chen; Yuting Wen; Xueqi Guo; Shiyong Zhao (BMC Oral Health)
Abstract Background Fibrous dysplasia (FD) is a self-limiting benign disease with slow progression in which the normal bone is replaced by dysplastic fibrous tissue. The craniofacial skeleton is one of the most commonly affected areas, and it can create unique challenges in dental implant therapy. This case aims to report an unusual presentation of FD localized in the alveolar crest bone of the edentulous site, causing special obstacles to implant placement, and provide a diagnostic and treatment process that may be referenced. Case presentation A 32-year-old female patient presented with an abnormal expansion of the alveolar crest on the edentulous site of the mandibular first molar, which caused insufficient inter-arch space and pseudo-pocket in the adjacent teeth, previous medical history of residual root that existed for many years before tooth extraction was identified retrospectively. FD was diagnosed by the clinical, radiographic, and pathological examination, and the curettage was performed to remove abnormal bone tissue and obtain adequate restorative space for further implant therapy. This intervention was followed by histologically confirmed healing and successfully integrated implant placement. Conclusion We described an unreported pathogenic site of FD that occurred at the alveolar ridge of the edentulous site, which ended up with satisfactory oral implant rehabilitation through 5-year sequential diagnosis and treatment.